الاستراتيجيات المستخدمة في تعديل السلوك للأطفال ذوي الاحتياجات الخاصة من طرف المعلمين واقتراحات لتطويرها)دراسة ميدانية في بعض مراكز التربية الخاصة في الجزائر( - كريمة جوال (Hakika (The Truth) Journal for Social & Human Sciences, 2025)
The current study aims to identify the behavior modification strategies employed by special education teachers and propose suggestions for their development. The study adopts a descriptive methodology and applies a research tool--a behavior modification strategies questionnaire designed by the researcher--on a random sample of 30 teachers from several special education centers in Algiers. The results revealed the following: Teachers use positive reinforcement strategies at a rate of 6.6%, negative reinforcement at 16.6%, reinforcement schedules at 3.3%, and differential reinforcement at 20%, while negative punishment is used at a rate of 50%. Teachers frequently use strategies such as extinction, prompting, modeling, chaining, generalization, visual aids, and stimulus control, with rates ranging from 53.3% to 100%. Strategies such as role-playing, relaxation, shaping, alternative behavior, visual schedules, social stories, behavioral contracts, and overcorrection are less frequently used, with rates ranging from 3.3% for role-playing through theater and relaxation to 40% for alternative behavior.